2009
DOI: 10.3109/09513590903056811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methotrexate administration on status of some essential trace elements and antioxidant enzymes in pregnant rats in late gestation

Abstract: We report for the first time that effect of MTX administration in pregnancy is not associated with significant alteration in disposition of essential trace elements. However, the effect of drug administration on antioxidant enzyme status in pregnant women cannot be excluded while using the drug in clinical states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Methotrexate treatment increased Zn-SOD activity although it had no effect on GSH-Px activity in rats [24,25]. In the present study, methotrexate increased serum zinc levels in the patients with RA enhancing the activity of Zn-SOD [24,25]. No changes in serum copper and selenium levels were observed.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Methotrexate treatment increased Zn-SOD activity although it had no effect on GSH-Px activity in rats [24,25]. In the present study, methotrexate increased serum zinc levels in the patients with RA enhancing the activity of Zn-SOD [24,25]. No changes in serum copper and selenium levels were observed.…”
Section: Discussioncontrasting
confidence: 63%
“…It induces metallothionein synthesis, which has been shown to sequester free radicals [20]. Methotrexate treatment increased Zn-SOD activity although it had no effect on GSH-Px activity in rats [24,25]. In the present study, methotrexate increased serum zinc levels in the patients with RA enhancing the activity of Zn-SOD [24,25].…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Surprisingly, GSH level, both in serum and liver showed elevation in the group treated with MTX, an effect unexpected from a cytotoxic drug and attributed to interference with GSH metabolism. 16,17 Regardless to the observed rise in GSH level, this did not stop MTX from damaging the liver; which may suggest mechanisms other than oxidant/antioxidant involved in MTX induced hepatotoxicity that cannot be opposed by MTX induced rise in GSH, and that all MTX treated rabbits showed hydropic degeneration on histopathological examination.…”
Section: Discussionmentioning
confidence: 82%
“…In another study, SOD and GPX values were significantly higher, but TAC was significantly lower in MTX-treated animals as compared with the controls (p<0.05). 18 Further, Shema-Didi et al 19 showed that one-year pomegranate juice (PJ) intake decreased oxidative stress and inflammation in hemodialysis patients. While Faria et al 20 demonstrated the protective effect of PJ against systemic oxidative stress in mice.…”
Section: Resultsmentioning
confidence: 99%